A 7-Amino Acid Peptide Mimic from Hepatitis C Virus Hypervariable Region 1 Inhibits Mouse Lung Th9 Cell Differentiation by Blocking CD81 Signaling during Allergic Lung Inflammation. (20th March 2020) - Zhao, Wanzhou; Tan, Conghao; Yu, Xi; Yu, Ruihe; Mei, Qibing; Cheng, Yun
Abstract : T helper (Th) cells orchestrate allergic lung inflammation in asthma pathogenesis. Th9 is a novel Th cell subset that mainly produces IL-9, a potent proinflammatory cytokine in asthma. A 7-amino acid peptide (7P) of the hypervariable region 1 (HVR1) of hepatitis C virus has been identified as an important regulator in the type 2 cytokine (IL-4, IL-5, and IL-13) immune response. However, it is unknown whether 7P regulates Th9 cell differentiation during ovalbumin- (OVA-) induced allergic lung inflammation. To address this, we studied wild-type mice treated with 7P and a control peptide in an in vivo mouse model of OVA-induced allergic inflammation and an in vitro cell model of Th9 differentiation, using flow cytometry, cytokine assays, and quantitative PCR. The binding of 7P to CD81 on naïve CD4 + T cells during lung Th9 differentiation was determined using CD81 overexpression and siRNA knockdown analyses. Administration of 7P significantly reduced Th9 cell differentiation after OVA sensitization and exposure. 7P also inhibited Th9 cell differentiation from naïve and memory CD4 + T cells in vitro . Furthermore, 7P inhibited the differentiation of human Th9 cells with high CD81 expression from naïve CD4 + T cells by blocking CD81 signaling. CD81 siRNA significantly reduced Th9 cell differentiation from naïve CD4 + T cells in vitro . Interestingly, CD81 overexpression in human naïve CD4 + T cells also enhanced Th9 development in vitro . These data indicate that 7P may be a good candidate for reducing IL-9 production in asthma.